(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Hospital pharmacists play a crucial role in achieving favourable patient outcomes, there are however limited studies about their job satisfaction in Nigeria. Objectives: The study aimed at evaluating the job satisfaction of hospital pharmacists, factors influencing it and also sought to assess the views of policy-makers regarding the satisfaction of hospital pharmacists in Osun State, Nigeria. Methods: The study was a cross-sectional survey of 91 out of 110 practicing pharmacists in secondary and tertiary hospitals in Osun State of Nigeria. Data were collected with two sets of pre-tested questionnaire, one for the hospital pharmacists and another for policy-makers. Descriptive statistics including frequencies, percentages and weighted averages were used to summarize the data while Exact Binomial Test was used to test for relationships at 5% level of significance. Results: The factors influencing job satisfaction were found to include age of the pharmacists (ꭓ2 = 193.287, p = .000), job relevance in the hospital (Weighted Average (WA) = 4.43) and status job confers (WA = 3.95). It also showed that adequate remuneration (WA = 2.43), advancement opportunities (WA = 2.87) and time for personal life (WA = 2.88) influenced their job satisfaction. Policy-makers agreed (WA = 3.52) with the respondents that work environment favoured employee satisfaction. Conclusions: The hospital pharmacists were satisfied with their jobs. Certain aspects of the job like remuneration, advancement opportunities, time for personal life will need improvement to further increase their job satisfaction.